KEPEMIMPINAN SPIRITUAL (SPIRITUAL LEADERSHIP) GURU SEKOLAH DASAR DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK - Siti Maulidatul Mukaromah (Jurusan PGMI FTIK IAIN Metro Lampung, 2018)
This article discusses the model of spiritual leadership of elementary school teachers in the character formation of students, which teacher leadership in the classroom influences whether or not the character possessed by the students. The research method usedlibrary reserarch. Library research is a research conducted by researchers by collecting a number of books, magazines, leaflets pertaining with problems and research objectives. The findings in the research of spiritual leadership applied by elementary school teachers in leading the students, teachers always lead by using heart with the charactheristic are taqwa, tawakal and tawadhu (3T). So, the studentswill have a good character.